Antennas based on low-cost thermoplastic polymer substrates for communication in the industrial, scientific and medical radio band. Issue 11 (24th July 2019) - Gil, I.; Colom, X.
ABSTRACT: This work addresses the design guidelines, manufacturing process and experimental test of antennas based on low cost and low loss thermoplastic polymer substrates. The proposed antennas are based on patch topologies operating at the 2.45 GHz industrial scientific and medical radio band for wireless body area network applications. Several substrates composed of ethylene vinyl acetate (EVA) and reused waste chicken feather have been used. Electromagnetic simulations and experimental results have been compared. The reported results reveal a notable performance in terms of antenna parameters: return loss, radiation pattern, realized gain, and efficiency. In particular, EVA and EVA with chicken feathers present competitive return losses and gains. Moreover, on-voxel analysis reveals that specific absorption rate standards are satisfied for both public and occupational sector with a significant safety margin. The study demonstrates the viability of those polymer substrates to deploy cost-effective solutions for wireless electronic systems including reusable material substrates.